2002
DOI: 10.1007/s00347-002-0655-4
|View full text |Cite
|
Sign up to set email alerts
|

Supplementierungsmedikamente beim Einsatz der Larynxmaske in der Kataraktchirurgie

Abstract: S-Ketamin had no significant effect on IOP and vitreous pressure during phacoemulsification. It offers a safe "handling" of patients because of a high spontaneous breathing rate and lower concentration compared to Ketamin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…To minimize this potential hemodynamic instability, several combinations of pharmacological drugs have been introduced to anethesia protocols. Although some clinical studies on cataract surgery have demonstrated that anesthetic drugs such as propofol and fentanyl do not significantly change IOP, the effect of ketamine on IOP remains controversial [5]. It is widely known that ketamine is not used alone as an induction agent because it causes excessive secretions and does not adequately suppress airway reflexes.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize this potential hemodynamic instability, several combinations of pharmacological drugs have been introduced to anethesia protocols. Although some clinical studies on cataract surgery have demonstrated that anesthetic drugs such as propofol and fentanyl do not significantly change IOP, the effect of ketamine on IOP remains controversial [5]. It is widely known that ketamine is not used alone as an induction agent because it causes excessive secretions and does not adequately suppress airway reflexes.…”
Section: Introductionmentioning
confidence: 99%